Regeneration of Raja (Musa AAB Group) and Kepok (Musa ABB Group) bananas on various stages of in vitro culture - Nazihah, Shafira Puti; Rahayu, Megayani Sri; Armini Wiendi, Ni Made (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2023)
Banana group can be divided into two groups based on their method of its utilization. Banana group that can be eaten immediately after ripening is called